PENERAPAN MODEL MIND MAP UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA MATERI KERAJAAN ISLAM DI INDONESIA - Pratama, Raka Nurmawan; Kurnia, Dadang; Djuanda, Dadan (Jurnal Pena Ilmiah, 2019)
Problem in this research is lack of student understanding about history of Islamic empire material in Indonesia. This is caused by use of social science learning models less capable arousing motivation student for study. Based on this backgroundthe researcher formulated, that is ; (1) how to implement mind map models to improve student understanding in the material history of the Indonesian Islamic empire. (2) how to improve student understanding on the material history of the Indonesian Islamic empire. Then, based on formulation of the problem researcher formulate research objectives, that is ; (1) to describe implementation mind map models to improve student understanding on the material history of the Indonesian Islamic empire. Model in this research use the model classroom action research Kemmis and Mc Taggart. This research implemented in two cycles. Every cycles consist of one learning and four phase, planning, implementation, observation, and reflection. The research instrument in use is observation sheet, field notes, documentation, assessment Guidelines, and interview sheet. the data analysis technique used is techniques for analyzing qualitative data and quantitative data. Based on research that has been carried out on cycles one, average value of student understanding 69, on cycles two increased to 80. These result shows that mind map model can increased student understanding on the material history of the Indonesian Islamic empire.